Investigation of cerium-139 radioisotope adsorption by conducting polymer composite - Olatunji, Michael Adekunle; Khandaker, Mayeen Uddin; Mahmud, Habibun Nabi Muhammad Ekramul (Springer Verlag (Germany), 2018)
Cerium is an abundant rare earth element, with several stable and radioactive isotopes. Due to its numerous industrial applications, cerium radioisotopes are common components of liquid radioactive wastes. We investigated the removal of 139Ce radionuclide from wastewater by adsorption using composite of polypyrrole with wood sawdust, as a model for other cerium radioisotopes. The composite material was characterized by Brunauer–Emmett–Teller, field emission scanning electron microscopy and Fourier transform infrared spectroscopy techniques. Effects of pH, initial ion concentration and temperature on the uptake amount of 139Ce were investigated by batch adsorption. The results indicated that the uptake amount of cerium ion increased with a rise in pH to optimum value of 8.0 and contact time of 120 min. The pseudo-second-order kinetics was found to best fit the kinetic data, while the isotherm data showed a good fit to both the Langmuir and Freundlich models. The maximum sorption capacity of 6.57 ± 0.54 mg/g was estimated by the Langmuir model. Thermodynamic studies indicated that the adsorption is feasible, spontaneous and endothermic in nature. The radiation hardness of polymer composite was also investigated by exposing it to 60Co gamma source. Irradiation had practically no significant effect on the sorption performance of as-prepared polymer composite.